An improved viscoelastic model for tufted carpet yarn. Issue 1 (2nd January 2018) - Huang, Shuang; Chi, Xinfu; Xu, Yang; Sun, Yize
Abstract: To overcome the problem that the existing mathematical model cannot characterize the viscoelastic properties of tufted carpet yarn completely and accurately, an improved viscoelastic model is built using the semi-empirical method. Using the test data of creep and stress relaxation, the parameters of the improved model are determined. Through the evaluation of fitting effect, the optimal mechanical model to characterize the viscoelastic properties of tufted carpet yarn is obtained. The results show that compared with the standard linear model, the improved model is more suitable to characterize viscoelastic mechanical properties of tufted carpet yarns, such as the creep and stress relaxation properties, which provides a solid theoretical foundation for analysis of vibration characteristics and dynamic tension control of tufted carpet yarn.